La pensée politique de René Lévesque dans ses chroniques au Journal de Montréal et au Jour entre 1970 et 1976 - Lagacé, François (Université de Sherbrooke, 2001)
Keywords: Jour (Le); Journal de Montréal (Le); Lévesque; René

Fascisme et anti-fascisme autour de la guerre civile espagnole dans le Québec des années trente - Désy, Caroline (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Guerre; Idéologies

Le théâtre d'environnement de Maurice Demers, un art d'intervention sociale et politique - Roy, Michel (Bulletin d'histoire politique, 2001)
issued: 2001-22-00
Keywords: Théâtre

La présence communiste au Québec (1929-1939) ou la présence de "l'homme au couteau entre les dents" - Dansereau, Bernard (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Communistes

Le théâtre communiste québécois ou l'écrasement de l'art par la politique - Milot, David (Bulletin d'histoire politique, 2001)
issued: 2001-22-00
Keywords: Communistes; Théâtre

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Le discours des acteurs de la crise d'octobre 1970 dans la presse francophone de Montréal (1971-2000) - Leroux, Manon (Université du Québec à Montréal, 2001)
Keywords: Crise d'octobre; Front de Libération du Québec

Daniel Coussirat (1841-1907): la vie et l’œuvre d’un intellectuel franco-protestant - Hamelin, Charles (Université de Montréal, 2001)
Keywords: Protestants

Libéralisme, nationalisme et catholicisme dans la pensée politique de Claude Ryan au Devoir (1962-1978) - Marcil, Olivier (Université de Montréal, 2001)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan; Claude

Le nationalisme anglo-québécois à travers "The Gazette" et le "Montreal Daily Star" pendant la Seconde Guerre mondiale - Lacasse, Chantal (Université de Montréal, 2001)
Keywords: Montreal Gazette; Montreal Star; Nationalisme

Nationalisme et antinationalisme dans le Québec des années 1935-1939 - Bégin, Yves (Université de Montréal, 2001)
Keywords: Nationalisme

Le Front d’action politique (FRAP) à Montréal: de la naissance aux élections (1969-1970) - Comby, Marc (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2001)
Number: 2
Keywords: Groupes populaires; Partis politiques; Élections